2018
DOI: 10.1002/ecs2.2383
|View full text |Cite
|
Sign up to set email alerts
|

Salty fertile lakes: how salinization and eutrophication alter the structure of freshwater communities

Abstract: The quality of freshwater ecosystems is decreasing worldwide because of anthropogenic activities. For example, nutrient over‐enrichment associated with agricultural, urban, and industrial development has led to an acceleration of primary production, or eutrophication. Additionally, in northern areas, deicing salts that are an evolutionary novel stressor to freshwater ecosystems have caused chloride levels of many freshwaters to exceed thresholds established for environmental protection. Even if excess nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 59 publications
(131 reference statements)
1
22
1
Order By: Relevance
“…Another study showed 1,000 mg Cl − /L reduced chlorophyll a content and biomass of the macroalgae Nitella sp. (Lind et al, 2018). Some evidence suggests that road salt can have a stimulating effect on phytoplankton abundance (Fay & Shi, 2012;Hintz et al, 2017).…”
Section: Diatoma Vulgaris Encyonema Caespitosum Pinnularia Microstamentioning
confidence: 99%
“…Another study showed 1,000 mg Cl − /L reduced chlorophyll a content and biomass of the macroalgae Nitella sp. (Lind et al, 2018). Some evidence suggests that road salt can have a stimulating effect on phytoplankton abundance (Fay & Shi, 2012;Hintz et al, 2017).…”
Section: Diatoma Vulgaris Encyonema Caespitosum Pinnularia Microstamentioning
confidence: 99%
“…We used a full-factorial design of species kept in the absence and presence of competing species along five different salinity environments (adding appropriate levels of NaCl to the protist medium to reach concentrations of 0, 0.5, 1, 2, and 4 g/l respectively). These NaCl concentrations correspond to a natural, unpolluted freshwater pond or lake (0 g/l), as well as realistic and currently experienced as well as future predicted environmentally relevant NaCl concentrations 64 , 65 . The experiment was conducted in 50 ml centrifuge tubes.…”
Section: Methodsmentioning
confidence: 72%
“…Although increasing, present‐day concentrations of sodium and chloride from road salts are unlikely to affect the biota of Lake George. Some of the most sensitive lake organisms can tolerate much higher salt concentrations before being impacted (Evans and Frick ; Elphick et al ; Roe and Patterson ; Hintz et al ; Hintz and Relyea ; Lind et al ; Sinclair and Arnott ). For instance, low water hardness increases the toxicity of chloride from road salts triggering negative effects around 64 mg Cl − L −1 for sensitive zooplankton species (Elphick et al ).…”
Section: Discussionmentioning
confidence: 99%